Sintesis Hidrogel Poli(N-Vinil-2-Pirolidon-Asam Tartrat) secara Iradiasi Gamma dan Karakterisasinya - SWASONO R. TAMAT; ERIZAL ERIZAL; CHAIRIL GUNAWAN (Fakultas Farmasi Universitas Pancasila, 2008)
Synthesis of poly(N-vinyl pyrolidone-g-tartaric acid) hydrogel using gamma irradiation had been carried out in two steps. First, irradiation of various concentrations of N-vinyl pyrolidone (NVP) byvarious irradiation doses. The yield of this process was determined by a gravimetric method. Hydrogel with the highest yield was selected for the second step: immersion in various concentrations of tartaric acid (TA) solution followed by irradiation. The yield (grafting percentage) was indirectly determined by a titrimetric method. All hydrogels were tested for their swelling ability (%) in solution of Various pH. The results showed that both NVP concentration and irradiation dose, and also interaction of the two, influenced the yield (gel fraction). The highest gel fraction (99.52%) was obtained from 70% NVP and 40 kGy dose. The result also showed that both TA concentration and irradiation dose, as well asinteraction of the two, influenced the grafting percentage. The highest grafting percentage (42.03%) was obtained by 0.8% TA and 40 kGy dose; while this hydrogel swelled 44.41 times in a pH 8 solution and swelled 42.2 times in a saline solution. The swelling capacity was slightly higher than the SNI 16- 6363-2000 requirement for sanitary napkins, however, lower than the ISO 17190-5-2001 requirement for baby napkins.